Re-visioning Negative Archetypes of Disability and Deformity in Fantasy: Wicked, Maleficent, and Game of Thrones - Donnelly, Colleen Elaine (Disability Studies Quarterly, 2016)
Fantasy and horror often exploit disabled people, presenting them as embodiments of terror and evil. In contemporary fantasy, we sometimes see archetypically evil characters redefined primarily by the telling of their backstories to provide rationale for their behavior and to evoke sympathy or pity from the audience. Pity often places the viewer in the position to seem benevolent while masking the ways that disabled people are often treated as inferior, different, and are isolated from the rest of society. In Wicked, Maleficent, and Game of Thrones, we are asked to confront the judgments and behaviors in which spectators and society engage. Instead of reaffirming the views and values of society, these works question and denounce our consumption of the stereotypes we have learned and our often unexamined behaviors towards those who are often treated as "others."